2020
DOI: 10.1016/j.rser.2020.110322
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effect of renewable electricity on employment in the United Kingdom

Abstract: Assessment of the employment impact of renewable electricity technologies is generally implemented through either complex and data-intensive methods (such as Computable General Equilibrium models) or simplistic approaches, normally focused on specific energy generation technologies, such as employment factors. In contrast, this article proposes a transparent and easily reproducible econometric methodology based on the Vector Error Correction model that uses aggregated and widely available data. The model is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…This finding is reliable with Arvanitopoulos and Agnolucci (2020), who noted that renewable energy production contributes to stimulating employment in the United Kingdom. This study also reported that 1 GWh increase in annual renewables creates 4.7 new jobs in the short-run period and 3.5 jobs in the long period.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is reliable with Arvanitopoulos and Agnolucci (2020), who noted that renewable energy production contributes to stimulating employment in the United Kingdom. This study also reported that 1 GWh increase in annual renewables creates 4.7 new jobs in the short-run period and 3.5 jobs in the long period.…”
Section: Resultssupporting
confidence: 86%
“…Hillebrand et al (2006) revealed that renewable energy production has importance in their formulation of the labor market. Therefore, we follow Arvanitopoulos and Agnolucci (2020) and adopt the following long-run model:…”
Section: Model and Methodsmentioning
confidence: 99%
“…Therefore, the results of the model do not include indirect employment and induced employment. Some scholars also apply econometric methods such as vector error correction model and panel data analysis to the impact of renewable energy on employment (Arvanitopoulos and Agnolucci 2020 ), analyze the relationship between renewable energy installed capacity and job creation, and propose that every 1% increase in renewable energy generation capacity will increase employment by 0.48% (Proença and Fortes 2020 ).IRENA and Greenpeace International use the work intensity or employment factor (Vosniadou et al 2018 ) to measure the number of jobs gained from an increase in capacity or investment in given energy technology, and the results are highly transparent (Zhou et al, 2020 ). Rutovitz and Atherton ( 2009 ) elaborate on the EF approach to job creation potential in a low-carbon energy environment of the future as proposed in the Greenpeace Energy Plan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The long-term response of employment to renewable electricity consumption in the U.K. is examined by Arvanitopoulos and Agnolucci (2020) with evidence supporting 3.5 jobs in response to 1 GWh increase in yearly renewable energy. For China, Mu et al (2018) reveal that about 15,800 and 45,100 direct and indirect jobs are induced by the expansion of wind power and solar PV by just 1 TWh, respectively.…”
Section: Why Energy-employment Nexus In Oil-importing and Oil-exporting Countries?mentioning
confidence: 99%
“…The long‐term response of employment to renewable electricity consumption in the U.K. is examined by Arvanitopoulos and Agnolucci (2020) with evidence supporting 3.5 jobs in response to 1 GWh increase in yearly renewable energy. For China, Mu et al .…”
Section: Why Energy‐employment Nexus In Oil‐importing and Oil‐exporting Countries?mentioning
confidence: 99%